2015
DOI: 10.18632/oncotarget.6313
|View full text |Cite
|
Sign up to set email alerts
|

SET antagonist enhances the chemosensitivity of non-small cell lung cancer cells by reactivating protein phosphatase 2A

Abstract: SET is known as a potent PP2A inhibitor, however, its oncogenic role including its tumorigenic potential and involvement in the development of chemoresistance in non-small cell lung cancer (NSCLC) has not yet been fully discussed. In present study, we investigated the oncogenic role of SET by SET-knockdown and showed that SET silencing impaired cell growth rate, colony formation and tumor sphere formation in A549 cells. Notably, silencing SET enhanced the pro-apoptotic effects of paclitaxel, while ectopic expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 47 publications
(58 reference statements)
1
32
0
Order By: Relevance
“…More interestingly, our group and others have found that the activity of SET is associated with the development of resistance to standard anticancer drugs, namely chemotherapies or target therapies, in various malignant diseases (Agarwal et al, 2014;Cristobal et al, 2015;Hung et al, 2015Hung et al, , 2016Zhang et al, 2015). For example, ectopic expression of SET diminished the effects of paclitaxel against non-small cell lung cancer (Hung et al, 2015) and oxaliplatin against colon cancer (Cristobal et al, 2015). The present study elaborated the impact of SET dysregulation in relation to RT, another important anticancer modality, thus adding to current knowledge.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…More interestingly, our group and others have found that the activity of SET is associated with the development of resistance to standard anticancer drugs, namely chemotherapies or target therapies, in various malignant diseases (Agarwal et al, 2014;Cristobal et al, 2015;Hung et al, 2015Hung et al, , 2016Zhang et al, 2015). For example, ectopic expression of SET diminished the effects of paclitaxel against non-small cell lung cancer (Hung et al, 2015) and oxaliplatin against colon cancer (Cristobal et al, 2015). The present study elaborated the impact of SET dysregulation in relation to RT, another important anticancer modality, thus adding to current knowledge.…”
Section: Discussionmentioning
confidence: 91%
“…SET is a novel oncoprotein that affects the behavior of cancer cells in multiple ways (von Lindern et al, 1992;Al-Murrani et al, 1999;Fan et al, 2003;Arnaud et al, 2011;Switzer et al, 2011;Hung et al, 2015Hung et al, , 2016. Initially, set gene was identified as a novel fusion partner of a putative oncogene, can, in a patient with acute undifferentiated leukemia (von Lindern et al, 1992;Adachi et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings indicated that I2PP2A can be a direct target of isolie. In addition to isolie, other structurally unrelated chemicals also enhance the activity of PP2A via interfering with the binding between PP2A and I2PP2A [31, 32]. The molecular pathways underlying isolie-provoked p65 dephosphorylation at Ser536 and subsequent HCC cell apoptosis are schematically summarized in Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…Although multiple inhibitors of the downstream PI3K and MAPK signaling pathway have been developed, they have largely been unsuccessful in clinical trials due to high toxicity and limited efficacy [51, 52]. Since loss of PP2A regulatory subunits and overexpression of SET and CIP2A have all been reported in lung cancer [53-55], the Westermarck group investigated the role of PP2A suppression in driving resistance to kinase inhibitors in KRAS-driven lung cancer cell lines. This was done using a high-throughput drug screen in which two KRAS-driven NSCLC cell lines were treated with 230 different kinase inhibitors.…”
Section: Pp2a Activationmentioning
confidence: 99%